A Review of Bacterial Interactions With Blow Flies (Diptera: Calliphoridae) of Medical, Veterinary, and Forensic Importance. (26th December 2016) - Tomberlin, Jeffery K.; Crippen, Tawni L.; Tarone, Aaron M.; Chaudhury, Muhammad F. B.; Singh, Baneshwar; Cammack, Jonathan A.; Meisel, Richard P.
Abstract : Blow flies are commonly associated with decomposing material. In most cases, the larvae are found feeding on decomposing vertebrate remains; however, some species have specialized to feed on living tissue or can survive on other alternate resources like feces. Because of their affiliation with such septic environments, these insects have close associations with microbes. Historically, a tremendous amount of research focused on these insects due to their veterinary importance. Within the past 40 yr, efforts have expanded this research to include areas such as systems ecology, forensics, and even wound debridement (maggot) therapy. Initial research efforts examining the relationship between microbes and these insects were hampered by the technology available. However, with the advent of high-throughput sequencing and modern molecular techniques, new avenues of research examining these interactions have opened up. The purpose of this article is to highlight the research exploring the interactions between microbes and blow flies with regards to blow fly biology, the application of such information to benefit humanity, and potential future pathways of research.